ANALISIS SISTEM INFORMASI PEMBERIAN KREDIT PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK (STUDI PADA BANK BRI (PERSERO) TBK KANTOR UNIT SYAMSUDIN NOOR) - Rory Handriano (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,This research aims to determine the management activities of management in Banking, especially concerning the methods Analysis System financial information in order to implement the precautionary principle (Prudential Banking) in channeling credit by one state-owned bank in South Kalimantan, where specifically the analysis was conducted to determine real picture, systematic, and accuracy in terms of Lending.The method used is descriptive qualitative method to view the credit information system is adequate and can be implemented comprehensively in PT BRI (Tbk) Unit Office Syamsudin Noor, so that the level of risk value NPL / Non Performing Loan (NPL) can be reduced.This research found that the technical Lending by PT BRI (Tbk) Unit Office Syamsudin Noor is still not right. This is caused because of the number of human resources or expertise available is still limited, and there are no sudden inspection (Supriser Auditor) to see the data that is required, so often happens abuse. Data verification procedures, interviews with prospective customers, and transactions of collateral that is often performed by a customer service (due to lack of human resources) resulted in a double data verification, where the elements of the documents are missing terms or data that is not requested by the customer service. Side implementation of direct visits (On The Spot) to a prospective borrower is still not optimal, so that the precautionary principle and the bank's operations do not run in accordance with established procedures.